Design of Hybrid Solar Wind Energy System in a Microgrid with MPPT Techniques - D. Chinnakullay Reddy; S. Satyanarayana; V. Ganesh (Institute of Advanced Engineering and Science, 2018)
DC Microgrid is one feasible and effective solution to integrate renewable energy sources as well as to supply electricity. This paper proposes a DC microgrid with enhanced Maximum Power Point Tracking (MPPT) techniques for wind and solar energy systems. In this paper, the PV system power generation is enhanced by introducing a two-model MPPT technique that combines incremental conductance and constant voltage MPPT algorithms. Also, for the Wind Energy Conversion System (WECS) with pitch angle controlling technique, an Optimal Power Control MPPT technique is added. The Space Vector Pulse Width Modulation technique is introduced on grid side converter to improve the supply to the grid. The performance of proposed system is analyzed and the efficiency obtained with these methods is enhanced as compared with the previous methods.